1978
DOI: 10.1351/pac197850040291
|View full text |Cite
|
Sign up to set email alerts
|

Photostabilization of macromolecules by excited state quenching

Abstract: -One approach to imparting long-terrn outdoor stability to polymeric systems is to add to them small amounts of compounds which will quench the electronic excitation energy associated with specific Chromophores as a result of photon absorption. Carbonyl groups, hydroperoxides and singlet molecular oxygen (or its precursors) are Chromophores cornrnonly believed to be involved in the photodegradative mechanisrns for numerous hydrocarbon polymers. Nevertheless, carbonyl quenching additives are rarely effective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(UV radiation is known to be present in low temperature He plasma [18]). Discoloration of PET was already observed on UV-treatment -where the photodegradation was attributed to the ester carbonyl group as chromophore [19] -and on ion beam treatment [20]. It was emphasised that after the onset of irradiation, new chromophores might become important [19].…”
Section: Changes In Chemical Composition and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…(UV radiation is known to be present in low temperature He plasma [18]). Discoloration of PET was already observed on UV-treatment -where the photodegradation was attributed to the ester carbonyl group as chromophore [19] -and on ion beam treatment [20]. It was emphasised that after the onset of irradiation, new chromophores might become important [19].…”
Section: Changes In Chemical Composition and Structurementioning
confidence: 99%
“…Discoloration of PET was already observed on UV-treatment -where the photodegradation was attributed to the ester carbonyl group as chromophore [19] -and on ion beam treatment [20]. It was emphasised that after the onset of irradiation, new chromophores might become important [19]. In another publication, the build up of conjugated aromatic structures was considered a part of the colour formation process [21].…”
Section: Changes In Chemical Composition and Structurementioning
confidence: 99%
“…The changes، in the intensities off the stretching absorptions bands of the carbonyl group was used to follow then extent off polymers degradation during irradiation, because then intensities off these bands are directly proportional to، the extents of degradation [25] Results figures (2)(3)(4)(5) show that the carbonyl index (ICO) are decreasing with increase weight ratio concentration of additives and shown that additive concentrations of 0.5% by weight gave، the best results. concentration (0.1-0.5% for C1 additive(.…”
Section: Fig(1): Ft-ir Spectra Of Pvc Samples Stabilized With 05% (mentioning
confidence: 99%
“…It is widely recognized that ultraviolet radiation (UV) in sunlight (wavelengths between 280 nm and 400 nm) is an important factor causing photodegradation too some organic polymers such as poly vinyl chloride [3]. UV radiation causes photo oxidative degradation which results in breakdown of polymeric (C-C) bonds, and produces free radical and reduces the molecular weights, causing deterioration off mechanical properties and leading too useless materials, after an unpredictable times [4,5] Poly(vinyl chloride) is ones of then important commercial polymers, commonlys used in many industrial fields which including electronic, architecture, chemical engineering, transportation and packaging [6,7] When exposed vinyl chloride polymers too light at 250-350 nm typical signs off degradation appears in polymer samples [8] and include the following. physical properties such ass loss of impact strength, changes in color, cracking, loss of elongation and tensile strength or chalking off the surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 The sequence illustrates the principle, and examination of Fig. 1 shows that energy transfer to additive molecules from initiating chromophores, from carbonyl groups and from singlet oxygen could in principle be photoprotective.…”
Section: Excited State Quenchingmentioning
confidence: 99%